1999
DOI: 10.1111/j.1751-1097.1999.tb08257.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser Photolysis of Chromium(lll) Porphyrins in Toluene Solutions. Effects of Oxygen on the Photodissociation Yields of the Axial Ligands

Abstract: The effects of oxygen on the photochemical reactions of chromium(1II) porphyrins with axial nitrogenous bases in toluene are studied by nanosecond laser flash photolysis. The photodissociation of the axial bases is confirmed to occur via both the excited states 4S1 and @TI (and/or 4T1) on the basis of the effect of oxygen on the quantum yield of photoreaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Clearly, dioxygen plays a crucial role in nanoparticle synthesis in THF. Dioxygen has nearly equal solubility in toluene and THF (Bunsen solubility coefficients = 0.22 and 0.24, respectively , ), so the effect is not one of O 2 concentration, but of its absence. We next speculate on the role of O 2 in the reaction and the THF solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, dioxygen plays a crucial role in nanoparticle synthesis in THF. Dioxygen has nearly equal solubility in toluene and THF (Bunsen solubility coefficients = 0.22 and 0.24, respectively , ), so the effect is not one of O 2 concentration, but of its absence. We next speculate on the role of O 2 in the reaction and the THF solvent.…”
Section: Resultsmentioning
confidence: 99%
“…We have been particularly interested in the dynamics of the photoinduced axial ligand dissociation and association reaction of the chromium(III) porphyrins. Theoretical and photophysical studies revealed that the excited singlet and triplet states of the porphyrin π system weakly interact with the central chromium atom ( S = 3/2) to give 4 S 1 , 2 T 1 , 4 T 1 , and 6 T 1 excited states and that the lowest and second lowest excited states, 6 T 1 and 4 T 1 , are in thermal equilibrium. , Meanwhile, laser photolysis of chromium(III) porphyrins in solution causes photoinduced axial ligand ejection as well as other various photoinduced phenomena. Since the photodissociated ligand undergoes a recombination reaction to yield the parent metalloporphyrins, laser photolysis is one of the key methods to elucidate the dynamics of the axial ligand binding. An earlier study has shown that the axial ligand of chromium(III) porphyrins is fairly labile compared with those of other chromium(III) complexes having non-porphyrin ligands .…”
Section: Introductionmentioning
confidence: 99%
“…The rate for the decay of the triplet state is much faster than that of (I - )Rh III TPP, and thus, the transient spectrum for the triplet state is obtained by subtracting the transient spectrum measured at 2 μs from that at 30 ns. With the use of the absorbances, D T (λ) and D 0 (λ), of the excited triplet state and the ground state of (I - )(PPh 3 )Rh III TPP at the wavelength λ, the absorbance change, Δ D (λ), of the transient spectrum of the triplet state is expressed as , The variable number, k , is the function of the energy of a laser pulse and ranges 0 < k < 1.0. Equation 9 is transformed to If k is appropriate, the plot of D T (λ) vs λ gives the absorption spectrum of 3 [(I - )(PPh 3 )Rh III TPP]*.…”
Section: Resultsmentioning
confidence: 99%
“…Equation 9 is transformed to If k is appropriate, the plot of D T (λ) vs λ gives the absorption spectrum of 3 [(I - )(PPh 3 )Rh III TPP]*. We assume here that the triplet spectrum of (I - )(PPh 3 )Rh III TPP in the Soret band region is not distorted. , The value k = 0.6 ± 0.05 gives a smooth absorption band centered at 490 nm. Thus, the triplet absorption spectrum is obtained by the plot of D T (λ) vs λ at k = 0.6 ± 0.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation